REACTIVE CHANGES IN THE STOMACH WHEN EXPOSED TO AN ENERGY DRINK - Abdullaev J.I.; Usmonov R. Dj.; Khudaybergenov B. E. (Journals Park Publishing, 2024)
The study involved administering Red Bull energy drink per os to rats weighing 180-220 grams for 10, 30, and 60 days, and the morphological changes in the stomach mucosa were investigated. Signs of hypertrophy of the glandular layer of the stomach mucosa, necrotic markers, and thickening of the mucosal layers were identified in the experimental group. These changes were more pronounced towards the end of the experiment.
Keywords: Stomach, postnatal ontogenesis, energy drink, mucosal layers.